Pemberdayaan Masyarakat Kampung Germas Desa Pinggir: Pembuatan Taman Asman Toga Untuk Mendukung Kesehatan Keluarga - Haq, Rynda Naashehatul; Agus Darmawan; Aulia, Syifana (Jurnal Bina Desa, 2025)
Community empowerment is a crucial aspect in efforts to improve health at the village level, especially through community-based initiatives. This community service focuses on the implementation of the "Empowerment of the Germas Village Community in Pinggir Village: Making an Asman Toga Garden to Support Family Health" program which aims to increase awareness and practice of healthy living in Sengon Hamlet, Pinggir Village through the creation of an asman toga garden. The asman toga garden, which is a special garden for medicinal plants, is designed to provide easy access to the community to medicinal plants that are beneficial for health. The creation of an asman toga garden not only increases community knowledge about medicinal plants but also significantly improves family health practices. In addition, active community involvement in the creation and maintenance of the garden strengthens the sense of ownership and responsibility for their own health. The location was chosen in Sengon Hamlet because Sengon Hamlet is a Germas Village that is a pioneer in the healthy community movement in Pinggir Village. The creation of the Asman TOGA garden is expected to improve health levels and reduce the effects of community dependence on circulating chemical drugs.